2004
DOI: 10.1093/nar/gnh173
|View full text |Cite
|
Sign up to set email alerts
|

Detecting tissue-specific regulation of alternative splicing as a qualitative change in microarray data

Abstract: Alternative splicing has recently emerged as a major mechanism of regulation in the human genome, occurring in perhaps 40-60% of human genes. Thus, microarray studies of functional regulation could, in principle, be extended to detect not only the changes in the overall expression of a gene, but also changes in its splicing pattern between different tissues. However, since changes in the total expression of a gene and changes in its alternative splicing can be mixed in complex ways among a set of samples, sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 25 publications
(33 reference statements)
8
64
0
Order By: Relevance
“…At the early time point, genes regulated at the transcriptional levels are significantly enriched in GO terms associated with immune defense and cytoskeletal functions, whereas genes regulated at the AS level are enriched for GO terms associated with cell-cycle regulation. Independent roles for AS and transcription in the regulation of gene expression programs are consistent with previous results (Le et al 2004;Pan et al 2004Pan et al , 2006. Collectively, these observations suggest that separate mechanisms acting at the AS and transcriptional levels are typically used to achieve distinct functional outcomes in a diverse range of physiological contexts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…At the early time point, genes regulated at the transcriptional levels are significantly enriched in GO terms associated with immune defense and cytoskeletal functions, whereas genes regulated at the AS level are enriched for GO terms associated with cell-cycle regulation. Independent roles for AS and transcription in the regulation of gene expression programs are consistent with previous results (Le et al 2004;Pan et al 2004Pan et al , 2006. Collectively, these observations suggest that separate mechanisms acting at the AS and transcriptional levels are typically used to achieve distinct functional outcomes in a diverse range of physiological contexts.…”
Section: Discussionsupporting
confidence: 88%
“…These results raised the question as to the extent of the overlap between genes regulated at the AS and transcript levels in the context of the rapid responses that occur in Jurkat cells following stimulation. In previous studies, we and others observed that different subsets of genes are regulated at the AS and transcript levels in differentiated mammalian tissues (Le et al 2004;Pan et al 2004). Consistent with these previous studies, at both early and late activation points, the majority of the genes that show a change at the level of AS do not show a change at the transcript level (Fig.…”
Section: Monitoring Changes In As During Jurkat Cell Activationmentioning
confidence: 76%
“…Methods for designing and interpreting data from AS-specific arrays (e.g. Le et al, 2004;Shai et al, 2006) are still in their infancy, but it is encouraging to note that there are now companies that state this as their primary goal. Development of methods to examine transcriptome wide changes in AS, in parallel with global gene expression phenotypes, will enable new ways to examine genetic mechanisms and molecular pathways by which variable phenotypes are generated; this in turn will allow examinations of how allelic variation affects plastic responses.…”
Section: Jh Mardenmentioning
confidence: 99%
“…which have been proven to play critical roles in the process of spermatogenesis and steroidogenesis. Various approaches have been used to analyze these tissueexclusively expressed genes including suppression subtractive hybridization (SSH), 8) differential display reverse transcription-polymerase chain reaction (RT-PCR), 9) microarray, 10) and whole genome approach analysis. 11) The UniGene database (http://www.ncbi.nlm.nih.gov/unigene) is a collection of sequences of individual clones from the cDNA libraries of various organs.…”
mentioning
confidence: 99%